Comparison of virulence of Francisella tularensis ssp. holarctica genotypes B.12 and B.FTNF002-00. Issue 1 (December 2016) - Kreizinger, Zsuzsa; Erdélyi, Károly; Felde, Orsolya; Fabbi, Massimo; Sulyok, Kinga; Magyar, Tibor; Gyuranecz, Miklós
Abstract Background Two main genetic groups (B.12 and B.FTNF002-00) ofFrancisella tularensis ssp.holarctica are endemic in Europe. The B.FTNF002-00 group proved to be dominant in Western European countries, while strains of the B.12 group were isolated mainly in Northern, Central and Eastern Europe. The clinical course of tularemia in the European brown hare (Lepus europaeus ) also shows distinct patterns according to the geographical area. Acute course of the disease is observed in hares in Western European countries, while signs of sub-acute or chronic infection are more frequently detected in the eastern part of the continent. The aim of the present study was to examine whether there is any difference in the virulence of the strains belonging to the B.FTNF002-00 and B.12 genetic clades. Results Experimental infection of Fischer 344 rats was performed by intra-peritoneal injection of three dilutions of a Hungarian (B.12 genotype) and an Italian (B.FTNF002-00 genotype)F. tularensis ssp.holarctica strain. Moderate difference was observed in the virulence of the two genotypes. Significant differences were observed in total weight loss values and scores of clinical signs between the two genotypes with more rats succumbing to tularemia in groups infected with the B.FTNF002-00 genotype. Conclusions Results of the experimental infection are consistent with previous clinical observations and pathological studies suggesting thatF. tularensis ssp.holarctica genotype B.FTNF002-00 has higher pathogenic potential than the B.12 genotype.